Investigation of SLA4A3 as a candidate gene for human retinal disease. Issue 1 (December 2016) - Downs, Louise; Webster, Andrew; Moore, Anthony; Michaelides, Michel; Ali, Robin; Hardcastle, Alison; Mellersh, Cathryn
Abstract SLC4A3 has been shown to cause retinal degeneration in a genetically engineered knockout mouse, and in a naturally occurring form of canine progressive retinal atrophy considered to be the equivalent of retinitis pigmentosa in humans (RP). This study was undertaken to investigate ifSLC4A3 coding variants were implicated in human retinal degeneration.SLC4A3 exons were amplified and sequenced in 200 patients with autosomal recessive retinal degeneration who had no known molecular diagnosis for their condition, which included 197 unrelated individuals with suspected RP and three individuals with other forms of retinal disease. Three rare variants were identified that were predicted to be potentially pathogenic, however each variant was heterozygous in a single patient and therefore not considered disease-causing in isolation. Of these three variants, SNP-3 was the rarest, with an allele frequency of 7.06x10−5 (>46, 000 exomes from the ExAC database). In conclusion, no compound heterozygous or homozygous potentially pathogenic variants were identified that would account for recessive RP or retinal degeneration in this cohort, however the possibility remains that the rare variants identified could be acting with as yet undiscovered mutations in introns or regulatory regions.SLC4A3 remains an excellent candidate gene for human retinal degeneration, and with the advent of whole exome and whole genome sequencing of cohorts of molecularly unsolved patients with syndromic and non-syndromic forms of retinal degeneration, SLC4A3 may yet be implicated in human disease.